(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: To date, particular emphasis is being put to correction of preoperative corneal astigmatism in phacoemulsification, since approximately 30% of the world’s population has astigmatism of at least 0.75D which results in decreased visual acuity after cataract surgery. Purpose: To assess the effect of corneal astigmatism on refractive outcomes of phacoemulsification with implantation of a spheric intraocular lens (IOL). Material and Methods: We retrospectively analyzed the outpatient medical records of 39 patients (50 eyes) who received phacoemulsification with a spherical IOL and had corneal astigmatism of 0.5-3.75D (as assessed by keratometry). Eyes were divided into four groups based on the degree of corneal astigmatism. We assessed changes in visual acuity and corneal astigmatism and refractive outcomes of cylindrical correction at one month after surgery. Results: The greater the presurgical astigmatism, the lower was uncorrected visual acuity at one month after surgery. There was no significant difference (р > 0.05) in change in corneal astigmatism values after phacoemulsification. In group 1 (preoperative astigmatism of 0.75 D or less) and group 2 (preoperative astigmatism of 1.0 to 1.5 D), the mean increase in visual acuity after cylindrical refractive correction was 10% or less, and had no significant impact on the quality of vision. In group 3 (preoperative astigmatism of 1.75 to 2.5 D) and group 4 (preoperative astigmatism of 2.75 D or more), the mean increase in visual acuity was 15% and 25%, respectively. Conclusion: Surgically induced astigmatism after phacoemulsification had no substantial impact on refractive outcomes. When planning refractive outcomes for eyes with astigmatism after cataract surgery, it should be taken into account that implanting a spherical IOL is acceptable only for eyes with an amount of preoperative astigmatism of 0.75 D or less and vertical axis of astigmatism. Cataract patients with preoperative corneal astigmatism of >0.75 D will require implantation of a toric IOL or a plan for astigmatism correction with another method.